Pengaruh Dana Pihak Ketiga (DPK), Return On Asset (ROA), Dan Capital Adequacy Ratio (CAR) Terhadap Likuiditas (FDR) Pada Bank Umum Syariah Tahun 2017-2022 - Ahmad Muhzazin; Anzu Elvia Zahara; Sri Rahma (Maslahah : Jurnal Manajemen dan Ekonomi Syariah, 2023)
The banking industry is one of the businesses that relies on trust which is the main foundation of banking activities, namely confidence from the public as a Islamic banking service user, grows well for an Islamic banking can be seen from the financial performance itself. Today’s liquidity is very important for Islamic banks in carrying out activities, whether to overcome urgent needs, meet customer demand to financing, providing flexibility in achieving interesting and profitable investment opportunities so as not to inhibit sharia banking itself. In this study aims to determine the Effect of Third Party Fund (Dpk), Return On Asset (Roa), And Capital Adequacy Ratio (Car) On Liquidity (Fdr) At the Sharia Bank of General Sharia Year 2017-2022. This study used the type of Quantitative Research using secondary data acquired from the official www.ojk.go.id This study was carried out using a multiple linear regression analysis method that has the results of the study that Third Party Fund negatively affects Financing Deposit Ratio which is evidenced with -thitung> ttabel (-2,605> 1.720). The Return On Asset did not significantly affect Financing Deposit Ratio which was evidenced by thitung <ttabel (1.487 <1.720). Capital Adequacy Ratio has no significant effect to Financing Deposit Ratio which is evidenced by -thitung <ttabel (-1,315 <1.720). As well as Third Party Funds, Return On Asset, Capital Adequacy Ratio Has a simultaneous effect on Financing Deposit Ratio which is evidenced by Fstatistik <0.05 (0.000 <0.05) and Fhitung Ftabel (16.647> 39). With an effect of 0.714 or 71% on FDR at Bank Syariah Public and the remaining 29% are influenced by other variables not included in this study.